Star architecture projects. The assessment of spatial economic effects by means of a spatial incidence analysis - Dreher, Johannes; Alaily-Mattar, Nadia; Thierstein, Alain (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
Following the inauguration of the Guggenheim Museum Bilbao, designed by the star architect Frank Gehry, numerous cities have developed star architecture projects that try to emulate the ‘Bilbao Effect’ in the hope of triggering positive impacts for tourism and socio-economic development. However, as many projects do not achieve the set goals, their role as catalysts for urban development is debatable. We argue that the temporal and spatial economic dimension of the effects of star architecture projects – which are hardly discussed in existing literature – is crucial to assess the contribution of such projects for urban regeneration. The Kunsthaus Graz in Austria serves as a case study where we apply and modify the approach of the ‘spatial incidence analysis’ to assess the socioeconomic and intertemporal effects of a publicly funded, star architecture project. The spatial incidence analysis is closely related to the cost-benefit analysis, but takes into consideration wider aspects of the spatial distribution and intertemporal development of three dimensions of effects: payment flows, goods and services, and utility. We identify the following key findings by applying a combination of quantitative and qualitative methods: the operation of the Kunsthaus Graz provides an inflow of purchasing power for the municipality of Graz; the Kunsthaus Graz has positive, long-term effects in the fields of tourism marketing, civic pride and identification, creative industries and urban regeneration; the effects of the Kunsthaus Graz are spatially concentrated in the municipality of Graz.